Effect of Tiotropium Bromide on Airway Inflammation and Programmed Cell Death 5 in a Mouse Model of Ovalbumin-Induced Allergic Asthma - Juan Wang; Xiaolin Diao; Hong Zhu; Bei He (Canadian Respiratory Journal)
Rationale. We previously demonstrated increased expression of programmed cell death 5 (PDCD5) in asthmatic patients and ovalbumin-induced allergic asthma. International guidelines (GINA 2019) have included the use of tiotropium bromide for chronic treatment of the most severe and frequently exacerbated asthma in patients ≥6 years old, who do not have good response to inhaled corticosteroids. Objective. To explore the role of tiotropium and its effect on PDCD5 level in a mouse model of chronic asthma. Methods. We divided 12 female mice into 2 groups: untreated asthma (n = 6) and tiotropium-treated asthma (n = 6). The impact of tiotropium was assessed by histology of lung tissue and morphometry. Pulmonary function was tested by using pressure sensors. The number of cells in bronchoalveolar lavage fluid (BALF) was detected. Levels of PDCD5, active caspase-3, and muscarinic acetylcholine receptors M2 (ChRM2) and M3 (ChRM3) were examined. Results. Tiotropium treatment significantly reduced airway inflammation and remodeling in asthmatic mice and intensified the lung function. PDCD5 level was reduced with tiotropium (p<0.05). Moreover, active caspase-3 level was decreased with tiotropium (p<0.001), and ChRM3 level was increased. Conclusions. Tiotropium treatment may alleviate the pathological changes with asthma by regulating apoptosis.